Histone acetylation dynamics in repair of DNA double-strand breaks - Aricthota, Shalini; Rana, Paresh Priyadarshan; Haldar, Devyani (Frontiers in Genetics, 2022)
Packaging of eukaryotic genome into chromatin is a major obstacle to cells encountering DNA damage caused by external or internal agents. For maintaining genomic integrity, the double strand breaks (DSB) must be efficiently repaired, as these are the most deleterious type of DNA damage. The DNA breaks have to be detected in chromatin context, the DNA damage response (DDR) pathways have to be activated to repair breaks either by Non-Homologous End Joining or Homologous Recombination Repair. It is becoming clearer now that chromatin is not a mere hindrance to DDR, it plays active role in sensing, detection and repair of DNA damage. The repair of DSB is governed by the reorganization of the pre-existing chromatin, leading to recruitment of specific machineries, chromatin remodelling complexes, histone modifiers to bring about dynamic alterations in histone composition, nucleosome positioning, histone modifications. In response to DNA break, modulation of chromatin occurs via various mechanisms including post-translational modification of histones. DNA breaks induce many types of histone modifications, such as phosphorylation, acetylation, methylation and ubiquitylation on specific histone residues which are signal and context dependent. DNA break induced histone modifications have been reported to function in sensing the breaks, activating processing of breaks by specific pathways, and repairing damaged DNA to ensure integrity of the genome. Favourable environment for DSB repair is created by generating open and relaxed chromatin structure. Histone acetylation mediate de-condensation of chromatin and recruitment of DSB repair proteins to their site of action at the DSB to facilitate repair. In this review, we will discuss the current understanding on the critical role of histone acetylation in inducing changes both in chromatin organization and promoting recruitment of DSB repair proteins to sites of DNA damage. It consists of an overview of function and regulation of the deacetylase enzymes which remove these marks and the function of histone acetylation and regulators of acetylation in genome surveillance.